Fertilizer management strategies for legume based croping systems in the West African semiarid tropics - Bartiono, A.; Ndunguru, B.J.; Ntare, B.R.; Christianson, C.B.; Mokwunye, A.U. (1991)
A major constraint the smallholder farmer faces in the West African semi-arid tropics (WASAT) is the low productivity of soils, which is often combined with land and labor shortage, caused in part by low productivity of labor, lack of cash resources, and limited access to credit. Groundnut and cowpea are two of the predominant grain legumes in the WASAT; they are important components of the mainly cereal-based cropping system, the most important cereals being pearl millet and sorghum. Production of these legumes is low and unstable because of the lack of adaptable cultivars with some resistance to the major biotic and abiotic stress factors, inherent low fertility of soils, uncertain rainfall distribution, and the short duration of the growing season. A current review of literature reveals that nitrogen (N), phosphorus (P), calcium (Ca), magnesium (Mg), and molybdenum (Mo) are the most important nutrients limiting legume production in the WASAT. Improvement of legume-based production systems will depend on amelioration of the low soil fertility, use of appropriate fertilizers, improved cultural practices, and use of appropriate cultivars. This chapter discusses these aspects and highlights research findings at the ICRISAT Sahelian Center. Exxperiments on rotation of cereals with groundnut and cowpea are demonstrating that it is possible to intensify and sustain the cereal-legume-based cropping systems in this drought-prone region.